Operating expenses enhance employee productivity and strengthen anti-fragility in the pawnshop business causal evidence from double machine learning - Iman Supriadi; Mochamad Fatchurrohman (Economic Military and Geographically Business Review, 2026)
Background: Digital transformation has reshaped how firms convert operating expenses into productivity gains, especially in service-based and financial institutions. While prior studies emphasize cost efficiency and technological adoption as performance drivers, evidence on whether rising operating expenses generate positive productivity shocks remains inconclusive. The literature also has not fully examined whether firms can become anti-fragile, where increasing operational costs strengthen capability. This study estimates the causal impact of operating expense growth on employee productivity and examines whether a state-owned financial institution evolves toward an anti-fragile model post-pandemic. Methods: This study applies a quantitative causal inference approach using post-pandemic annual secondary data from Pegadaian’s audited financial and sustainability reports. Employee productivity is measured by revenue and net profit per employee, with operating expense growth as the main treatment and financial stability indicators as controls. Double Machine Learning isolates the pure causal effect while addressing non-linearity and endogeneity, supported by visual analysis to validate patterns and identify digital efficiency thresholds. Findings: The results show a positive and statistically meaningful causal effect of operating expense growth on revenue per employee, with a coefficient of 6,755.68, indicating that higher operational spending significantly enhances productivity. Visual evidence supports anti-fragility, as post-pandemic observations consistently exceed predicted productivity trends, with the peak deviation in 2024, suggesting a digital efficiency threshold where intangible investments yield disproportionate gains, reinforcing anti-fragility theory and extending the Solow residual toward digital capability accumulation. Conclusion: The study concludes that strategically managed operating expenses function as productivity-enhancing investments rather than cost inefficiencies, confirming the emergence of an anti-fragile business model. Novelty/Originality of this article: This article introduces a causal machine learning framework to operationalize anti-fragility in firm-level productivity analysis and identifies a digital efficiency threshold that has not been empirically documented in prior financial services research.